Gaspar Silveira Martins e o município "Silveira Martins": memória, identidade e patrimônio - Fenalti, Naiani Machado da Silva (2011)
The Professional Master's Thesis in Cultural Heritage had as a clause to elaborate the planning and historical background of an exhibition that treated about the historical relation of the city of Silveira Martins - founding members of the Quarta Colônia de Imigração Imperial of Rio Grande do Sul - with its patron, Gaspar Silveira Martins. Gaspar Silveira Martins was a politician from the second half of the nineteenth century, which belonged to the Liberal Party of Rio Grande do Sul, he was among other positions as minister, a senator and the president of the Province. During his political career he defended the arrival of European immigrants to Brazil, specifically; to Rio Grande do Sul, and such defense is manifested in the creation s political support of the Colonial Center in Santa Maria from Boca do Monte in 1877, the one which would root the Colony of Silveira Martins. So, aiming to spread the knowledge about the local/regional history as a cultural heritage to the community in the city and in the region of Silveira Martins, an exhibition was organized. It was used panels with text and images, relating to the Italian immigration, the creation of Quarta Colônia, the border character Gaspar Silveira Martins, and the today s city of Silveira Martins. This exhibition has the Silveira Martins City Hall s support that will launch in the municipal week in December of 2011.